Pelanggaran Prinsip Kerja Sama dalam Film Roman Komedi ‘Jatuh Cinta Seperti di Film-film’ Karya Yandy Laurens - Alfi Ashila; Citra Anggraini Puspita Sari; Nazwa Cahya Ardiyani; Chelsea Fidela Maritza Siam; Devita Nur Hadiyani; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Dies Oktavia Dwi Astuti (Lembaga Pengembangan Kinerja Dosen, 2026)
Violations of the cooperative principle frequently occur in dialogues of comedy films, one of which is the romantic comedy film Falling in Love Like in the Movies by Yandi Laurens. This study aims to identify and describe the forms of maxim violations of the cooperative principle found in the film, as well as to analyse the function of maxim violations in building character and conflict among characters. This study uses a descriptive qualitative approach. The data in this research consist of utterances between characters that contain violations of the cooperative principle. The research data were collected using observation and note-taking techniques, while the data analysis was conducted using equivalence methods. The findings of this study indicate violations of the maxims of quality, quantity, relevance, and manner. The aim of this research is to make theoretical contributions to the deve lopment of pragmatic studies, particularly regarding the cooperative principle and maxim violations in film dialogues, as well as the creation of humour, conflict, and character development in the characters. In addition, this research is also expected to serve as a reference and consideration for future research discussing similar topics.